Kult Trzygława w Szczecinie lat 20. XII stulecia. Między monolatrią a „dwuwiarą” - Rosik, Stanisław (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2019)
The cult of Triglav in the Polabian-Pomeranian territory in the 12th century confirms an evolution of the religious system of the local Slavic communities towards monolatry, largely affected by confrontation as well as a cultural dialogue with the Christian culture. At first, at the time of the Pomeranian missions of Saint Otto of Bamberg in the 1120s, attempts at suppressing the cult did not bring about long-term effects. However, a wave of the so-called pagan reaction led to some sort of a compromise made in Szczecin, leading to official coexistence of the cult of Triglav and the newly introduced cult of Jesus Christ. From the point of view of mythology, the competences of the two divine figures turn out to be convergent and universal, yet still, as part of the Szczecin “religious dualism”, no attempt was made to identify them (following the rule of interpretatio Slavica of the elements of Christianity). The belief in the autonomy of Triglav and Christ (“A German God”) was confirmed in Szczecin in the course of Otto’s evangelization which resulted in a Christian community in the city. The phenomenon of syncretism, present there until Otto’s second mission (1128), was therefore an attempt at maintaining unity in a religiously divided society following the first mission of the Apostle of Pomeranians (1124-1125).